2017
DOI: 10.1111/eth.12702
|View full text |Cite
|
Sign up to set email alerts
|

Do birds differentiate between white noise and deterministic chaos?

Abstract: Noisy, unpredictable sounds are often present in the vocalizations of fearful and stressed animals across many taxa. A variety of structural characteristics, called nonlinear acoustic phenomena, that include subharmonics, rapid frequency modulations, and deterministic chaos are responsible for the harsh sound quality of these vocalizations. Exposure to nonlinear sound can elicit increased arousal in birds and mammals. Past experiments have used white noise to test for effects of deterministic chaos on perceive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
(55 reference statements)
1
5
0
Order By: Relevance
“…Chaos is indeed a characteristic of calls associated with distress in a wide range of mammals [10,15,16,21,23] (this study). Additionally, at the perceptual level, Blumstein & Récapet [24] have shown that white noise (which shares some perceptual elements with deterministic chaos [50]) added to natural alarm calls of marmots induces potentially costly responses in these animals (reduced foraging activity). An earlier study also showed that chaos added to human nonverbal vocalizations increases the intensity of perceived negative, rather than positive, affective states [51].…”
Section: Discussionmentioning
confidence: 99%
“…Chaos is indeed a characteristic of calls associated with distress in a wide range of mammals [10,15,16,21,23] (this study). Additionally, at the perceptual level, Blumstein & Récapet [24] have shown that white noise (which shares some perceptual elements with deterministic chaos [50]) added to natural alarm calls of marmots induces potentially costly responses in these animals (reduced foraging activity). An earlier study also showed that chaos added to human nonverbal vocalizations increases the intensity of perceived negative, rather than positive, affective states [51].…”
Section: Discussionmentioning
confidence: 99%
“…Second, future research could explore psychoacoustical sensitivity to vocal roughness, and how discrimination thresholds might shift as a function of low-level properties of the acoustic context. Additionally, error management principles could be at play as listeners might be biased to over-detect nonlinearbased roughness in cases of possible danger (Blumstein, Whitaker, Kennen, & Bryant, 2017). Finally, research could examine whether context effects exist with signals that are not conspecific vocalizations, such as other animals' vocalizations/calls or synthetic alarm signals.…”
Section: Discussionmentioning
confidence: 99%
“…To minimize the effects of pseudoreplication (Kroodsma 1989, McGregor et al 1992), we randomly selected stimulus files for each trial from a library of 60 songs (one song from 60 different individuals) (Table S2, 15 each of E. t. adastus , E. t. brewsteri , E. t. extimus , and E. t. traillii ). We used white noise (i.e., random noise with equal energy at all frequencies) as our control because it covers the frequency bandwidth of Willow Flycatcher song (~ 1–7 kHz, Mahoney et al 2020) and experiments have shown that birds respond similarly to white noise and heterospecific songs (Blumstein et al 2017) so it is a robust stimulus to use as a baseline for responses to playback. Most focal birds received all treatments on the same day ( N = 116 of 119), with at least 30 min between successive trials (Prescott 1987).…”
Section: Methodsmentioning
confidence: 99%